2021
DOI: 10.1111/aogs.14260
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of HPV, p16, and p53 protein expression in vaginal cancer: A systematic review

Abstract: Introduction Human papillomavirus (HPV), p16, and p53 have been investigated as prognostic markers in various HPV‐related cancers. Within the field of vaginal cancer, however, the evidence remains sparse. In this systematic review, we have compiled the presently published studies on the prognostic significance of HPV and immunohistochemical expression of p16 and p53 among women with vaginal cancer. Material and methods We conducted a systematic search of PubMed, Embase, and Cochrane Library to identify relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…The prognostic significance of p53 expression in vaginal carcinoma has been investigated [ 27 , 28 , 29 , 30 , 31 , 32 ], but most did not find any. Moreover, since the reviewed cases predominantly consisted of squamous cell carcinoma rather than adenocarcinoma, the effect of TP53 mutation on the biological behavior and patient outcomes of vaginal adenocarcinoma remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic significance of p53 expression in vaginal carcinoma has been investigated [ 27 , 28 , 29 , 30 , 31 , 32 ], but most did not find any. Moreover, since the reviewed cases predominantly consisted of squamous cell carcinoma rather than adenocarcinoma, the effect of TP53 mutation on the biological behavior and patient outcomes of vaginal adenocarcinoma remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The early symptoms of this cancer are very subtle or lacking, so it is often diagnosed after the disease has deteriorated significantly, which makes the early diagnosis rate only 1.43%. With the development of bioinformatics, transcriptomic studies have found that some genes involved in tumorigenesis and metastasis are differentially expressed in tumor and normal tissues [72][73][74][75]. This opens the possibility for early detection of esophageal squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Third, external validation on a distinct population was not carried out because a sufficiently large sample from a different population was unavailable in a single healthcare center due to VC’s extreme rareness. Finally, human papillomavirus (HPV) has been argued to be positively associated with the survival of VC patients ( 48 ). However, the HPV status of VC patients was not available in the SEER database, so it could not be controlled.…”
Section: Discussionmentioning
confidence: 99%